Development and Evaluation of an Elder Abuse Forensic Nurse Examiner e-Learning Curriculum. (October 2020) - Kosa, Sarah Daisy; Du Mont, Janice; Macdonald, Sheila
In Ontario, Canada, there is a need for an easily accessible training for forensic nurse examiners on the provision of care for abused older adults. In this study, our objective was to develop and evaluate a novel elder abuse nurse examiner e-learning curriculum focused on improving the care provided to older adults. The curriculum was launched on an online learning management system to forensic nurses working across Ontario's hospital-based violence treatment centers in June 2019 and evaluated using pre- and post-training questionnaires that measured self-assessed changes in knowledge and skills-based competence related to providing elder abuse care. There were significant improvements pre- to post-training in self-reported knowledge and competence across all core content domains: Older Adults and Abuse; Documentation, Legal, and Legislative Issues; Interview with Older Adult, Caregiver, and Other Relevant Contacts; Initial Assessment; Medical and Forensic Examination; and Case Summary, Discharge Plan, and Follow-Up Care. As the curriculum enhanced the knowledge and skills associated with caring for abused older adults, it may have implications for training forensic nurse examiners and associated staff working in more than 25 countries internationally.